Diversity under local management - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2002)
The Growing Diversity Website was launched in May 2002 with dozens of case studies of successful agricultural biodiversity projects based on people s control and local knowledge, worldwide. Run by the Genetic Resources Action International...